KEPERCAYAAN DIRI DENGAN KESIAPAN KERJA SISWA KELAS XII DI SMKN X SALATIGA - Luthfiana Husna Isnaini; Sutarto Wijono (Journal of Innovation Research and Knowledge, 2025)
Work readiness is an important aspect for vocational high school (SMK) students in facing the demands of the workforce, and one psychological factor that contributes to it is self-confidence, which helps students adapt, make decisions, and confront professional challenges. This study aimed to examine the relationship between self-confidence and work readiness among twelfth-grade students at SMKN X in Salatiga using a quantitative correlational approach. The study involved 100 students selected by cluster sampling. The research instruments included a work readiness scale based on aspects from Caballero et al. (2011) and a self-confidence scale based on the theory of Lauster (2012). Data were analyzed using Pearson’s correlation. The results showed a positive and significant relationship between self-confidence and work readiness (r = 0,670; p < 0,001), indicating that higher levels of self-confidence are associated with higher levels of work readiness. These findings underscore the importance of school programs focused on enhancing students’ self-confidence to support the work readiness of SMK graduates